Studi Independent Web Development di PT. Kinema Systrans Multimedia - Vinanditha, Cherlin; Almigo, Nuzsep (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Certified Independent Study is a program organized by Merdeka Campus under the auspices of the Ministry of Education and Culture of Ristekdikti. In this program, there are many large companies that contribute, one of which is PT. KINEMA SYSTRANS MULTIMEDIA, where the program aims to provide opportunities for students to hone their abilities outside of their current majors, besides that this program aims for students to gain new knowledge, gain more relationships so that they can develop themselves for the future outside of the current lecture class. Web development is an individual or group learning program under the guidance of mentors to discuss learning while this program is running, learning is carried out with presenters by meeting online through zoom. In this program PT. Kinema Systrans Multimedia provides material such as UI & UX Design, Frontend, Backend, Cybersecurity, Cloud Computing, and Digital Marketing. which aims to enable students to build websites with national and international standards and be able to develop skills in the field of web development.